Effects of Job Peripherality and Personal Characteristics on the Job Satisfaction of Part Time Workers - Hom, Peter W. (Academy of Management Journal, 1979)
Sixteen groups of part time employees in a retail sales organization were created by classifying employees by the number of hours they worked per week and whether they were employed on a seasonal or steady basis. The groups showed different demographic profiles and levels of job satisfaction, but their patterns of job satisfaction were similar. When the relationships between demographic and attitudinal variables were statistically controlled, the effect of peripheral attachment and participation in the work force on job attitudes was virtually eliminated.